2011
DOI: 10.1111/j.1478-3231.2011.02485.x
|View full text |Cite
|
Sign up to set email alerts
|

Kaerophyllin inhibits hepatic stellate cell activation by apoptotic bodies from hepatocytes

Abstract: Kaerophyllin inhibited AB-induced LX-2 activation and migration with downregulation of Akt/ERK phosphorylations and NF-κB activity. Our study suggests a novel platform for screening anti-fibrotic compounds with ABs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Activation of NF-κB is linked to phosphorylation and proteolytic degradation of IκBα [16]. TNF-α is known as one of the strongest stimuli of NF-κB activity [23]. Indeed, we found that TNF-α induced phosphorylation of IκBα level in LX-2 cells compared with the normal group and the phosphorylation of IκBα was further induced in LX-2 cells pretreated with NLRC5-siRNA, whereas NLRC5-siRNA notably reduce cell survival.…”
Section: Discussionmentioning
confidence: 85%
“…Activation of NF-κB is linked to phosphorylation and proteolytic degradation of IκBα [16]. TNF-α is known as one of the strongest stimuli of NF-κB activity [23]. Indeed, we found that TNF-α induced phosphorylation of IκBα level in LX-2 cells compared with the normal group and the phosphorylation of IκBα was further induced in LX-2 cells pretreated with NLRC5-siRNA, whereas NLRC5-siRNA notably reduce cell survival.…”
Section: Discussionmentioning
confidence: 85%
“…24-well plates were added reporter lysis buffer (100 µl/well), and 20 µl cell lysate mixed with 100 µl luciferin in white 96-well plates. Luminescence was detected by luminometer-VICTOR2 Multilabel Counter (Perkin Elmer Inc., Waltham, MA, USA), as previously reported by us [27], [28].…”
Section: Methodsmentioning
confidence: 99%
“…HSC-T6 cells were seeded on collagen coated 24-well plates [28], [30], [31] at a density of 9×10 4 cells/well. After 24 hr serum starvation, a monolayer of cells was scratched by a 200 µl tip in serum-free medium.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of kaerophyllin from BS is described as previously reported [11]. The structure of kaerophyllin was identified by their spectroscopic method and comparison with the literature values [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Kaerophyllin did not affect hepatocyte viability. Using MTT assays, rat hepatocytes showed no cytotoxicity in the presence of kaerophyllin up to 60 μ m for 48 h [11].…”
Section: Methodsmentioning
confidence: 99%